Magic in the Cosmopolis of Rome - Gordon, Richard (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
Using examples from anthropological studies of radical shifts in the imaginaire of magic in modern African and Asian societies, this paper outlines the consequences both for small time ritual practitioners themselves and for the stereotypes of a specifically urban magic that followed the decision to move to the megacity of Rome, taken as emblematic of the case with other large cities in the ancient Mediterranean world. Given the highly dispersed nature of religious authority in the Greek and Roman political formations, and the attraction of religious entrepreneurship in hierarchically-organised societies with very limited social mobility, the religious field of larger conurbations was characterised by competition for social and religious capital between official and unofficial ritual practitioners, whereby the former were in a position to dominate the relevant discourse in their own interests. This domination produced new accusations of misuse of religious symbols associated with specifically urban magic, focused on the manipulation of emotions, child-snatching, and the use of human body-parts for nefarious ends. Historically, however, the major significance of the transition from the rural to the complex urban world was increased competition between practitioners, leading to innovation in methods and media, above all in the production of new types of protective amulet, and recourse to textuality.